Aspek Sosial, Ekonomi, dan Lingkungan Ekowisata Subak Sembung, Kelurahan Peguyangan, Kecamatan Denpasar Utara, Kota Denpasar, Provinsi Bali - TOGATOROP, TIO TAPIANTA; WIJAYANTI, PUTU UDAYANI; ANGGREINI, I. G. A. A. LIES (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.11, No.2, Desember 2022DO - 10.24843/JAA.2022.v11.i02.p36, 2022)
Social, Economic, and Environmental Aspects in Subak Sembung as Ecotourism, Peguyangan Village, North Denpasar District, Bali Bali is part of the Indonesian territory that relies on the agricultural sector to meet the needs of the community as well as to support its tourism activities. Subak Sembung has been conserved and inaugurated as an ecotourism site in 2014 by the Denpasar City Government. Currently, Subak Sembung has 103 hectares of land and it has the largest green land in the city center, then known as the lungs of Denpasar City. This research is conducted with the aim of analyzing the social, economic, and environmental aspects in Subak Sembung as ecotourism in Peguyangan Village, North Denpasar District, Bali. The sample size is 35 people and generated by using simple random sampling. The data analysis method used is the descriptive qualitative analysis. The results shows that Subak Sembung as ecotourism in terms of social aspects measured from three indicators, namely the high level of knowledge of farmers about ecotourism, positive responses of farmers to ecotourism, and high skills of farmers in farming. The economic aspect measured in terms of economic benefits is relatively high, and the environmental aspect can be said to be good in terms of natural resource conservation is fairly high and facilities in the form of counseling and coaching are carried out quite often.